Exploring the response of lianas to elevated atmospheric carbon dioxide (CO2) in a mature Australian forest remnant - Hickson, John Christopher (2024)
Atmospheric CO2 is rising globally and is set to increase by up to 50% over the next 50 years. Elevated atmospheric CO2 has direct effects on vegetation as well as indirect effects through changing climates. Consequently, it is a global research priority to understand the effects of elevated atmospheric CO2 so that we may better forecast how the earth’s ecosystems may be affected by climate change. Forests are responsible for the largest terrestrial uptake of atmospheric CO2. Thus, much of the research efforts into ecosystem response to elevated atmospheric CO2 has focused on trees and their role in forests. Consequently, this high impact research has excluded other woody forest plants such as lianas (woody vines), which are becoming increasingly more dominant in forests across the globe. Lianas are growing in biomass, and diversity, and are proliferating in many of the world’s forests, yet remain an underrepresented plant functional group in science. As structural parasites, and strong competitors, of trees, lianas negatively impact the fecundity, growth, and survival of host trees. In turn lianas negatively impact the ability of forests to absorb and sequester carbon, which may lead to long term changes to the carbon balance of forests. Much of our knowledge of lianas is biased towards the neo-tropics, however liana species have been found worldwide. Similarly, the responses of lianas to elevated atmospheric CO2 is still poorly understood and biased towards evidence from small scale experiments, which have been either short term or have focused on the experimental manipulation of juvenile lianas. This has led to a key knowledge gap into how canopy reaching lianas respond to long term increases in atmospheric CO2. There are few experimental sites capable of testing the effects of elevated atmospheric CO2 on vegetation. However, the EucFACE facility in Australia is a large-scale Free Air Carbon Enrichment (FACE) facility that hosts a locally abundant liana, Parsonsia straminea in the Eucalyptus tereticornis woodland, offering a unique opportunity to explore: i) how these lianas respond to elevated atmospheric CO2; and ii) to contrast these responses to the dominant tree species. This thesis applies a novel remote sensing approach to retrospectively examine the effects of elevated atmospheric CO2 on lianas and their hosts. This is achieved using Terrestrial Laser Scanning (TLS) surveys to examine increases in liana load, using a novel imaging analysis to examine canopy responses with a simplistic greenness ratio, and exploring the hyperspectral response of lianas and trees and relating the response to possible chemical changes. At the EucFACE forest, lianas were found to be increasing in stature, measured as the height which lianas could be detected (LAH), and liana load, or proportion of trees hosting lianas, throughout the experiment. Increases in LAH and liana load were similar in ambient and elevated CO2 treatments and were similarly constrained by a multiyear drought between 2018 and 2020. Lianas showed a pronounced increase in greenness to elevated atmospheric CO2 while the dominant trees were found to be insensitive to CO2 regime. Canopy greenness response to elevated CO2 was greatest during seasonal water limitation but was constrained by the multiyear drought in both treatments. Leaf responses to elevated atmospheric CO2 were examined with hyperspectral spectroscopy, finding that lianas had a pronounced response to elevated CO2 conditions compared to that of trees, but that the response was limited to the visible and red-edge spectra. These lianas presented a spectral response that indicates increasing leaf chlorophyll concentrations in response to elevated CO2 conditions, which contrasts with prior responses of woody plants in elevated atmospheric CO2. These results indicate that: a) liana proliferation is insensitive to elevated CO2 conditions, b) lianas are likely more secure against seasonal droughts in elevated CO2 conditions, c) lianas are more responsive to elevated atmospheric CO2 than co-occurring trees, and d) liana greenness, and likely productivity, is constrained by long term drought regardless of CO2 treatment. Thus, it is likely that the liana Parsonsia straminea is advantaged by elevated atmospheric CO2 in short term periods of water limitation, whereas Eucalyptus tereticornis appears to show signs related to plant stress when exposed to elevated atmospheric CO2.